Lifetime calculations in energy levels of Kr VII - Raineri, María Mónica (2017)
Calculations of the lifetimes for all experimentally known energy levels of the spectrum of the six times-ionized krypton (Kr VII) are presented. The relativistic Hartree–Fock method including corepolarization effects were used. The energy matrix was calculated using energy parameters adjusted to the experimental energy levels.Wealso present a calculation based on a relativistic multiconfigurational Dirac–Fock approach. For some energy levels, a comparison of these results with the bibliography data was made.